420 pounds of beans from 1 1/12 pounds of seed grown by W. Wood of Oak Park near San Luis Obispo, Cal - Frank Aston::::::photographer:::
Student outside of tent exhibiting sacks of beans. '420 pounds of Beans from 1-1/2 pounds of seed Grown by Wm W. Wood of Oak Park near San Luis Obispo, Cal.'